In vivo requirement for glutaredoxins and thioredoxins in the reduction of the ribonucleotide reductases of Escherichia coli - Gon, Stéphanie; Faulkner, Melinda J; Beckwith, Jon (Antioxidants & redox signaling, 2006)
Escherichia coli expresses three types of ribonucleotide reductases (RNRs) that utilize the redox chemistry of cysteine to catalyze the reduction of ribonucleotides. Upon reduction, the cysteines form a disulfide bond and must be reduced. The authors present in vivo studies that shed light on the mechanism by which these enzymes are regenerated. The class Ia enzyme, NrdAB, can be reduced by either the thioredoxins 1 and 2 or by glutaredoxin 1. The class Ib enzyme, NrdEF, is reduced in vivo by a dedicated glutaredoxin-like protein, NrdH. Despite its similarities to glutaredoxins, this protein is itself reduced by thioredoxin reductase in vivo. However, in the absence of thioredoxin reductase and NrdH, glutaredoxin 1 can partially replace NrdH. Despite their similar structures, the NrdEF and NrdAB RNRs differ in their abilities to function under low oxygen conditions. With only traces of oxygen present, NrdAB can allow some growth in the absence of the anaerobic enzyme NrdDG. NrdEF cannot. Furthermore, in anaerobiosis, E. coli is dependent for growth on class III RNR, NrdDG, and on having at least one of the two reductive systems, thioredoxin reductase or glutathione reductase. These findings indicate a role for these enzymes either for NrdDG reactivation or some other essential anaerobic process.